Solo International Futsal Academy - Islami, Muhammad Afkarul (2016)
The development of futsal in solo city very rapidly, it is characterized by the many accomplishments achieved by the teams from the city of Solo. Achievement futsal teams from cities solo is not followed by the construction of facilities and infrastructure are sufficient. Such as futsal courts having international standards. Therefore, in a design the building were able to accommodate all futsal activities in the city of Solo. The site selected for the construction of Solo International Futsal Academy is on the Way Pakel, Banjarsari, Surakarta. Site has an area of ± 77,000 m2. According to the regulations, the site is intended for educational buildings and sports. Therefore, it is suitable for sports activities and education for Solo International Futsal Academy. In the Solo International Futsal Academy are international standard stadium and also the practice field sized international standards. In addition, there are also educational buildings, dormitories players and mosques as a means of worship.